2018
DOI: 10.1007/s00264-018-4110-9
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous internal anterior fixation of pelvis fractures—which configuration of the InFix is clinically optimal?—a retrospective study

Abstract: Planned optimized configuration of the InFix with a rod-to-bone distance between 20 and 25 mm may reduce postoperative complications. Regarding LFCN damage, the rod-to-symphysis distance should not be more than 40 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In a multicentre review, 30% (21/91) of patients had LFCN irritation although in most cases it was self-limiting and improved once the implant was removed [5]. In line with this study, in our investigation the rate of LFCN injury was 33.3% (10/30) [23]. We first locked the screws at bilateral AIIS so that the pullout strength of the screw was mainly concentrated in the supra-acetabular region, where bone density is high.…”
Section: Biomechanical Characteristics Of Intact Modelsupporting
confidence: 86%
“…In a multicentre review, 30% (21/91) of patients had LFCN irritation although in most cases it was self-limiting and improved once the implant was removed [5]. In line with this study, in our investigation the rate of LFCN injury was 33.3% (10/30) [23]. We first locked the screws at bilateral AIIS so that the pullout strength of the screw was mainly concentrated in the supra-acetabular region, where bone density is high.…”
Section: Biomechanical Characteristics Of Intact Modelsupporting
confidence: 86%
“…We also only considered the ISD and did not account for the conical shape of the screw. The 1.5 cm spacing between the bone and head of the screw was an attempt to avoid compression of the femoral neurovascular bundle and opted for more conservative results considering a constant screw cross‐section. For future development of this study, an algorithm with the ability to evaluate all feasible trajectories for other angles should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The screw length was considered as the sum of the intraosseous depth and 15 mm distance that has been suggested as minimal gap between the bone and screw head to avoid impingement with soft tissues . The ISD of 120 mm was selected to characterize the extreme combination of the longest documented screw length used for extremely obese patients, and largest bone to rod distance documented in literature of 25 mm . The screw core diameter of the template was set to 4 mm as representative to a screw size of 6.5 mm …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A case series of LFCN irritation suggested that screws that are too deeply or insu ciently embedded in the bone and inadequate prebending of the rod can lead to irritation of the LFCN and sartorius muscle. To prevent this, a rod-to-bone distance of 20-25 mm (30-40 mm for obese patients) but <40 mm is recommended [23]. We rst locked the screws at bilateral AIIS so that the pullout strength of the screw was mainly concentrated in the supraacetabular region, where bone density is high.…”
Section: Risk Of Implant Failure and Micromotion In The Injury Modelmentioning
confidence: 99%